Dinamika Eksternal dan Dampaknya pada Pergerakan Harga Saham Jakarta Islamic Index: Analisis Risiko Geopolitik, Kebijakan Ekonomi, Harga Minyak, dan Inflasi - Az-Zahra, Annisa Yaspa; Mukhsin, Moh; Pardiansyah, Elif (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
Islamic stock prices can be influenced by global conditions both at home and abroad. This is because globalization is increasingly widespread and has a major influence on fluctuations in Islamic stock prices.  The purpose of this study is to analyze the effect of geopolitical risk, China's economic policy uncertainty, and world oil prices on the Jakarta Islamic Index stock price through inflation. The analysis method used is path analysis with panel data for the 2019-2023 period. The results showed that geopolitical risk had a negative and significant effect on inflation and stock prices of the Jakarta Islamic Index. China's economic policy uncertainty has no effect on inflation and the Jakarta Islamic Index stock price. World oil prices have a positive and significant effect on inflation and the stock price of the Jakarta Islamic Index. Inflation has no effect on the stock price of the Jakarta Islamic Index. Inflation is not able to mediate the effect of geopolitical risk, China's economic policy uncertainty, and world oil prices on the stock price of the Jakarta Islamic Index.